The Influence of Padeye Placement on Ship Block Lifting - Andi Mursid Nugraha Arifuddin; Muhammad Uswah Pawara (BRIN, 2022)
Nowadays, steel ship construction in Indonesia is dominated by the hull block construction method. This method can reduce man-hours as the ship is manufactured by a division of the hull into several sections/blocks; here, it can be worked in parallel. Once work is finished on these blocks and then proceeding to the main hull for assembling, the lifting operation is performed on the blocks during this erecting process. Lifting of ship blocks must be planned safely to avoid damage. One of the items that must be considered is the position of the padeye. The placement or installation of the padeye in the block during the lifting operation plays a vital role in the deformation and working stress of the block structure. Consequences if this is not observed, which van cause misalignment in the welding join path on ship bloks due to excessive plastic deformation and stress. Therefore, this study aims to simulate the placement of a padeye that results in minimum deformation and structural stress. The method used in this research is the stiffness method applied in computer programs. In this studied, it had been recorded that the structure on the ship blok is deformed and stressed at each padeye position. Based on the simulation from 23 positions of the padeye, the optimal position of the pad eye is at position 10 in simulation 2 with deformation of x, y, and z coordinates which are 7 mm, 2 mm, and 7 mm, respectively. Generrally, In this case shown the deck girder and longitudinal beam structure is dominantly subjected to high deformation and stress in several position. Keyword: Padeye, Ship Block, Lifting, Deformation, Stress.